In Situ Tunable Interaction with an Invertible Sign between a Fluxonium and a Post Cavity - D.G. Atanasova; I. Yang; T. Hönigl-Decrinis; D. Gusenkova; I. Pop; G. Kirchmair (PRX Quantum)
Quantum computation with bosonic modes presents a powerful paradigm for harnessing the principles of quantum mechanics to perform complex information processing tasks. In constructing a bosonic qubit with superconducting circuits, nonlinearity is typically introduced to a cavity mode through an ancillary two-level qubit. However, the spurious heating of the ancilla has impeded progress toward fully fault-tolerant bosonic qubits. The ability to in situ decouple the ancilla when not in use would be beneficial but has so far only been realized with tunable couplers or additional parametric drives. This work presents a novel architecture for quantum information processing, comprising a three-dimensional post cavity coupled to a fluxonium ancilla via a readout resonator. The intricate energy-level structure of this system results in a complex landscape of interactions, the sign of which can be tuned in situ by the magnetic field threading the fluxonium loop without the need for additional elements. Our results could significantly advance the lifetime and controllability of bosonic qubits.